Bid’ah from the Hadith Perspective: Study of Takhrij and Syarah Hadith - Pebriyani, Neng Tipa (Journal of Takhrij Al-Hadith, 2024)
This study aims to discuss the hadith about bid’ah. This study uses a qualitative approach by applying the decriftive-analytical method. The results and discussion of this study show that the status of the hadith is sahih which meets the qualifications of maqbul for the practice of Islam. This study concludes that the Hadith narrated by Muslim No. 3242 is relevant as a reference to be careful in doing something.